Heteroepitaxial growth of Cu2O films on Nb-SrTiO3 substrates and their photovoltaic properties. Issue 18 (15th December 2017) - Wang, K.; Gao, W.; Zheng, H.W.; Li, F.Z.; Zhu, M.S.; Yang, G.; Yue, G.T.; Liu, Y.K.; Zheng, R.K.
Abstract: In this paper, p -type Cu2 O thin films have been epitaxially grown on n -type semiconducting (001) oriented Nb-SrTiO3 (NSTO) substrates with different Nb doping concentration by pulsed laser deposition technique. X-ray diffraction and high resolution transmission electron microscopy reveal a cube-on-cube epitaxial relationship between Cu2 O and NSTO. It is found that the deposition temperature, the thickness of Cu2 O films and the Nb doping concentration of NSTO substrates have critical impact on the photovoltaic (PV) properties of the Cu2 O/NSTO heterojunction devices. A maximum PV performance is observed in ITO/Cu2 O/NSTO device when the deposition temperature, film thickness and Nb doping concentration of NSTO are 550 °C, 76 nm, and 0.7 wt% NSTO, respectively. The optimized PV output corresponds to the open circuit voltage, short-circuit current density, fill factor and photovoltaic conversion efficiency about 0.45 V, 1.1 mA/cm 2, 46% and 0.23%，respectively. This work offers an insight into the strategy for developing and designing novel optoelectronics of NSTO-based oxide heterostructures.